Crater Dimensions on the Dwarf Planets - Veronica J. Bray; Michael F. Zeilnhofer; S. J. Robbins; P. M. Schenk; Kelsi M. Singer; O. L. White; S. A. Stern; S. D. Benecchi; K. A. Durfey; H. A. Weaver; C. B. Olkin; J. R. Spencer; et al. (The Planetary Science Journal)
The icy dwarf planets of Pluto, Charon, and Ceres provide important geologic comparisons for each other as they possess similar gravities and experience impacts of similar velocities compared to larger planets and moons. Differences in their impact craters can therefore be attributed to differences in the impactor and/or target compositions. Craters on Ceres show taller rims than craters on Charon, but comparable internal crater dimensions (depth, wall slope, and peak size). It is possible that the non-ice component of the Ceres crust provides additional strength to this outer portion of the crater, maintaining less rim collapse during the modification stage of crater formation, while the warmer central crater region is controlled by the weakness of the icy component. The spreads in depth-to-diameter ratio and wall-slope values for the Pluto data set are not clearly related to preservation state, suggesting that fresh craters on Pluto possess a large variance in these crater dimensions compared to Charon. This could be due to the geologically diverse terrains and depositional histories at different latitudes and longitudes of Pluto. These provide different target properties for each impact, so that even pristine impact craters on Pluto could display a wide range in depths and wall slopes based on the different strength of the target in each area.